Anesthesia for pulmonary trunk aneurysmorrhaphy - João,Benedito Barbosa (2017)
Abstract Background and objectives: The aneurysm in the pulmonary trunk is a rare disease. Because of its location, a rupture can lead to right ventricular failure and sudden death. Aneurysmorraphy is the most widely used surgical treatment in these cases. The aim of this study is to report a successful balanced general anesthesia for aneurysmorraphy of pulmonary trunk. Case report: Male patient, 28 years, asymptomatic, diagnosed with an aneurysm in the pulmonary trunk. According to the location of the aneurysm and the consequent failure of the pulmonary valve, an aneurysmorraphy was indicated, with implantation of vascular-valvular prosthesis (valved tube). We opted for a balanced general anesthesia, seeking to prevent an increase in systemic and pulmonary vascular resistances, thus avoiding to cause stress on the wall of the aneurysmal vessel. Conclusions: A balanced general anesthesia, in combination with adequate ventilation to prevent elevation in pulmonary vascular pressure, was appropriate for surgical repair of an aneurysm in the pulmonary trunk.